2017
DOI: 10.1016/j.mineng.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dissolved oxygen on the bioleaching efficiency under oxygen enriched atmosphere

Abstract: The use of oxygen enriched air is a common practice in high-temperature bioleaching tests (> 70°C) to overcome oxygen solubility limitation and reduced the energy costs of the process. Air is usually preferred in medium and low-temperature operations mainly for technical and economic constraints. Nevertheless, under high-sulfide loading conditions -high-grade metal sulfide concentrates and high solids concentration -the microbial and chemical demand for oxygen is significantly increased during the bioleaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 30 publications
1
9
0
2
Order By: Relevance
“…Heterotrophic strains were studied by HZDR (Germany) while BRGM (France) and BGR (Germany) focused on autotrophic bacteria and optimization of operating parameters. It was shown that sparkling the bioreactors with oxygen enriched gas instead of air offers an interesting alternative process to provide an adequate oxygen supply in order to satisfy the oxygen demand, which allow operating at higher solid load [11]. Besides O2 enrichment, this study demonstrated that CO2 supplementation is required to avoid limitation of the leaching kinetics [12].…”
Section: Ecometals Projectmentioning
confidence: 83%
“…Heterotrophic strains were studied by HZDR (Germany) while BRGM (France) and BGR (Germany) focused on autotrophic bacteria and optimization of operating parameters. It was shown that sparkling the bioreactors with oxygen enriched gas instead of air offers an interesting alternative process to provide an adequate oxygen supply in order to satisfy the oxygen demand, which allow operating at higher solid load [11]. Besides O2 enrichment, this study demonstrated that CO2 supplementation is required to avoid limitation of the leaching kinetics [12].…”
Section: Ecometals Projectmentioning
confidence: 83%
“…obtained from the BRGM-KCC microbial consortium subcultured on pyrite tailings (Guezennec et al, 2017). The predominant micro-organisms in the culture are affiliated to the acidophilic genera Leptospirillum, Acidithiobacillus and Sulfobacillus.…”
Section: Growth Medium and Bacterial Culture The Inoculum Used For Tmentioning
confidence: 99%
“…In our experiments an agitation speed of 800 to 900 rpm was used, and therefore in the next stage of testing, it could be reduced to accelerate sulphide oxidation. Consideration should also be given to increasing the quantity of O 2 gas purged through the tanks as explored in [50,51]. Gwénaëlle Guezennec et al [51] reported that when dissolved oxygen (DO) ranged from 4 to 13 ppm in bioleaching experiments (51% pyrite; 20% w/w solids) healthy bacterial oxidizing activity was observed, with sulphide dissolution efficiency increasing with DO concentration.…”
Section: Optimal Conditions For Biooxidationmentioning
confidence: 99%
“…Consideration should also be given to increasing the quantity of O 2 gas purged through the tanks as explored in [50,51]. Gwénaëlle Guezennec et al [51] reported that when dissolved oxygen (DO) ranged from 4 to 13 ppm in bioleaching experiments (51% pyrite; 20% w/w solids) healthy bacterial oxidizing activity was observed, with sulphide dissolution efficiency increasing with DO concentration. However, when DO concentrations reached 17 ppm, a significant decrease of microbial activity (and O 2 consumption) was noted, showing there is a critical DO threshold.…”
Section: Optimal Conditions For Biooxidationmentioning
confidence: 99%